Early detection of odontoma in patients with clinical features of periodontal disease: a case report - Tetelepta, Febri EN; Adam, Andi M. (Journal of Case Reports in Dental Medicine, 2019)
Objective: Chronic periodontitis is an infection of the gingiva that causes damage to the soft tissues and tooth-supporting bones. Chronic periodontitis is usually a slowly progressive disease that does not cause the affected individual to feel pain. For most patients, gingival bleeding during oral cleansing procedures is a sign of reported disease. Odontoma is an odontogenic tumor, characterized by slow growth. The tumor consists of enamel, dentin, cementum and sometimes pulp tissue.Methods: A 38-year-old male patient complaints swollen gums on the right upper back region. Clinical examination showed the presence of gingiva swelling, fistula, and grade 3 teeth mobility. In the systemic condition of the patient, malaise, fever and lymphadenopathy were not found. The treatment plan includes subgingival scaling treatment as well as antibiotic therapy as initial therapy. Advanced treatment is then continued with curative therapy with surgical extirpation, periodontal surgery and bone graft.Results: The success of treatment is shown by controlled inflammatory as well as probing depth. The condition of the teeth and the dental-jaw relationship has been restored after treatment.Conclusions: Chronic periodontitis with odontoma indicates treatment options according to the severity of the disease, access to mechanical care, and the patient's systemic condition.Keywords: Bone grafting, Gingival overgrowth, Odontoma, Surgical flap.